SPIDER ENVENOMING OF DOG - CASE REPORT - Fernandes, H. S. [UNESP]; Sakate, M. [UNESP]; Cherubini, A. L. [UNESP]; Padovani, A. F. [UNESP]; Meneses, A. M. C. [UNESP] (Centro de Estudos de Venenos e Animais Peçonhentos - CEVAP, Universidade Estadual Paulista - UNESP, 2002)
This report refers to a female Pinscher treated at the Veterinary Hospital of the Botucatu School of Veterinary Medicine and Animal Husbandry (FMVZ)-São Paulo State University (UNESP), Botucatu, 14 hours after a suspected spider envenoming. The animal showed spastic limbs, dyspnea, salivation, hypothermia, muscular fasciculation, non-responsive mydriasis, and claudication of the right hindlimb. The spider was later identified by the Center for the Study of Venoms and Venomous Animals-CEVAP/UNESP, Botucatu as Phoneutria nigriventer. The treatment with potent analgesic was efficient.
Keywords: Spider envenoming; Phoneutria nigriventer; dog